1983
DOI: 10.1042/bj2150565
|View full text |Cite
|
Sign up to set email alerts
|

The serine proteinase chain of human complement component C̅1s. Cyanogen bromide cleavage and N-terminal sequences of the fragments

Abstract: Human complement component C1s was purified from fresh blood by conventional methods of precipitation and chromatography. The single-chain zymogen form was activated by treatment with C1r. Reduction and carboxymethylation then allowed the light chain and heavy chain to be separated on DEAE-Sepharose CL-6B in 8 M-urea. Liquid-phase sequencing of the light chain determined 50 residues from the N-terminus. CNBr-cleavage fragments of the light chain were separated by high-pressure liquid chromatography on gel-perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In this respect, it should be mentioned that plasmin degradation of the serine protease domain of C1 s was reported to result in the loss of C4 binding ability (14). In the same way, it has been suggested that C1 s may interact with the C4a moiety of C4 through acidic residues close to the active site (41). It may be hypothesized, therefore, that efficient positioning of C4 with respect to C1 s requires two types of interactions: (i) between the C4b moiety and the CCP modules and (ii) between the C4a moiety and the serine protease domain.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it should be mentioned that plasmin degradation of the serine protease domain of C1 s was reported to result in the loss of C4 binding ability (14). In the same way, it has been suggested that C1 s may interact with the C4a moiety of C4 through acidic residues close to the active site (41). It may be hypothesized, therefore, that efficient positioning of C4 with respect to C1 s requires two types of interactions: (i) between the C4b moiety and the CCP modules and (ii) between the C4a moiety and the serine protease domain.…”
Section: Discussionmentioning
confidence: 99%
“…The phenylthiohydantoin samples were analysed by chromatography on a Waters Resolve C18 reverse-phase column with a pH 5.0 acetate/acetonitrile buffer system (Carter et al, 1983).…”
Section: Automatic Amino Acid Sequence Determinationmentioning
confidence: 99%
“…This was performed on a TSK 2000 SW column with either 0.3 M-sodium phosphate, pH 6.9, or 0.08 M-sodium phosphate/0.32 M-NaCl/20% (v/v) Smith et al (1982) and Carter et al (1983).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%